WOUND HEALING PROCESS AND WOUND CARE - Suryadi, Iwan Antara; Asmarajaya, AAGN; Maliawan, Sri (E-Jurnal Medika Udayana; vol 2 no2 (2013):e-jurnal medika udayana)
Wound is a loss or discontinuity of tissue which happen because external factor disrupts the barrier of the body. Wound healing process can be classified into: hemostatic & inflammation phase, proliferation phase and remodelling phase. The physiological process of wound healing is influenced by some factors, abnormalities of this process will result in abnormal tissue. Wound care purpose is to assist these physiological process of wound healing effectifely in the shortest time possible. Wound care procedure vary based on the wound type but can be divided into two main point which is wound cleaning by irrigation or debridement and wound closure.
Keywords: wound, wound healing, wound care